KONSEP IBADAH DAN PRANATA SOSIAL PERIBADATAN INDONESIA - Agi Sukma Gumilar (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2019)
AbstractWorship is obligation for all moslem in the world. Because the purpose of people is created by Allah is worship to only one god. Indonesia is the biggest moslem country in the world and one of over populated country , there is many culture until make a sosial interaction between civil society.